Target prediction of candidate miRNAs from Oryza sativa for silencing the RYMV genome. (December 2019) - Jabbar, Basit; Iqbal, Muhammad Shahzad; Batcho, Anicet A.; Nasir, Idrees A.; Rashid, Bushra; Husnain, Tayyab; Henry, Robert J.
Graphical abstract: Highlights: This study presents a synergistic computational approach to predict microRNAs of rice which can potentially hybridize to and silence the RYMV genome. Based on this research, following osa-miRNAs have been found to be better potential candidates for genome silencing of Rice yellow mottle virus: osa-miR414 (ΔG: -25.26 kcal/mol), osa-miR1851 (ΔG: -19.81 kcal/mol) and osa-miR5158 (ΔG: -20.70 kcal/mol). The microRNAs identified can be further evaluated by in vitro assays for their RYMV genome silencing effect. This can help in generating RYMV resistant O. sativa varieties in the future. Abstract: In order to maintain a consistent supply of rice globally, control of pathogens affecting crop production is a matter of due concern. Rice yellow mottle virus (RYMV) is known to cause a variety of symptoms which can result in reduced yield. Four ORFs can be identified in the genome of RYMV encoding for P1 (ORF1), Polyprotein (processed to produce VPg, protease, helicase, RdRp4) (ORF2), putative RdRp (ORF3) and capsid/coat protein (ORF4). This research was aimed at identifying genome encoded miRNAs of O. sativa that are targeted to the genome of Rice Yellow Mottle Virus (RYMV). A consensus of four miRNA target prediction algorithms (RNA22, miRanda, TargetFinder and psRNATarget) was computed, followed by calculation of free energies of miRNA-mRNA duplex formation. A phylogenetic tree was constructed to portray the evolutionary relationships between RYMV strains isolated to date. From the consensus of algorithms used, a total of seven O. sativa miRNAs were predicted and conservation of target site was finally evaluated. Predicted miRNAs can be further evaluated by experiments involving the testing of the success of in vitro gene silencing of RYMV genome; this can pave the way for development of RYMV resistant rice varieties in the future.